2020
DOI: 10.1002/chir.23185
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical analysis of chiral amines, diamines, and amino alcohols: Practical chiroptical sensing based on dynamic covalent chemistry

Abstract: Practical chiroptical sensing with a small group of commercially available aromatic aldehydes is demonstrated. Schiff base formation between the electron‐deficient 2,4‐dinitrobenzaldehyde probe and either primary amines, diamines, or amino alcohols proceeds smoothly in chloroform at room temperature and is completed in the presence of molecular sieves within 2.5 hours. The substrate binding coincides with a distinct circular dichroism signal induction at approximately 330 nm, which can be correlated to the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Such a design motif has been widely used to detect small molecule amines from the gas phase, e.g. , in combination with emissive conjugated polymers, for which several excellent literature sources can be consulted. It is worth pointing out that many powerful probes and chemosensors for amines that are operational in organic solvents have already been reported, for instance, by the Wolf group. Intuitively, aforementioned amine-reactive probes such as ninhydrin can react with amines in general, even though this was not expected by the time ninhydrin was first described for amino acid detection. Very recently, Wolf and coworkers demonstrated that the chiral chromophoric adduct formed under mild conditions from the reaction of chiral amines with ninhydrin can be used for chirality sensing of the nonchromophoric amine analytes in a practically convenient and inexpensive method . We would like to refer the reader to the original literature and reviews , as we focus herein on those systems that operate in aqueous media.…”
Section: Amines (Other Than Amino Acids)mentioning
confidence: 99%
“…Such a design motif has been widely used to detect small molecule amines from the gas phase, e.g. , in combination with emissive conjugated polymers, for which several excellent literature sources can be consulted. It is worth pointing out that many powerful probes and chemosensors for amines that are operational in organic solvents have already been reported, for instance, by the Wolf group. Intuitively, aforementioned amine-reactive probes such as ninhydrin can react with amines in general, even though this was not expected by the time ninhydrin was first described for amino acid detection. Very recently, Wolf and coworkers demonstrated that the chiral chromophoric adduct formed under mild conditions from the reaction of chiral amines with ninhydrin can be used for chirality sensing of the nonchromophoric amine analytes in a practically convenient and inexpensive method . We would like to refer the reader to the original literature and reviews , as we focus herein on those systems that operate in aqueous media.…”
Section: Amines (Other Than Amino Acids)mentioning
confidence: 99%
“…The responses to 3 / 4 / 5 are much more sensitive, and the linear regions are 1.0 × 10 –7 –5.0 × 10 –5 M for 3 and 4 and 1.0 × 10 –7 –1.0 × 10 –4 M for 5 (Figures f and S38). The maximum obtained g factor of the Au­(I)-MPA-MPBA nanosheets is −0.048 ( 2 (D) ), −0.042 ( 3 ), −0.045 ( 4 ), and −0.041 ( 5 ), respectively (Figure e), which is extremely high in CD sensing. The association constants between Au­(I)-MPA-MPBA nanosheets and guests ( 2­(D) / 3 / 4 ) were calculated with these curves, and they are 66.74 M –1 ( 2 (D) ), 0.83 × 10 5 M –1 ( 3 ), and 0.66 × 10 5 M –1 ( 4 ) assuming 2 (D) , 3 , and 4 had approached the maximal g factors (details on the calculation are shown in the Supporting Information and Table S3; due to the fact that the CD signal induced by 5 may not reach the maximum for the limited solubility, the corresponding association constant was not calculated). The results suggest that the higher sensitivity (1.0 × 10 –7 M) for 3 and 4 than 2 (D) is because of their higher association constants.…”
Section: Resultsmentioning
confidence: 99%
“…With the fast development of combinatorial chemistry and parallel synthesis, rapid analysis of the efficiency of each asymmetric synthesis is in urgent need. Among various high-throughput analytical methods such as fast chiral chromatography, NMR, , and optical chiral sensing, circular dichroism (CD) spectral sensing is a very competitive one, owing to the low consumption of solvent, easy operation, and its capability to reveal the absolute configurations of analytes with quantum calculation. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] Chiroptical sensing has emerged in the last few decades and provided insightful information on the electronic and conformational properties of non-fluorescent chiral compounds in practical and sustainable ways. [33][34][35][36][37][38][39][40][41][42] The search for versatile reporters in the visible region of the electromagnetic radiation is ongoing to widen the range of applications and standardize these methods.…”
Section: Introductionmentioning
confidence: 99%